Pantai Lampuuk dan Dampaknya Terhadap Perekonomian Masyarakat - Anisah Anisah; Riswandi Riswandi (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2015)
The study aims at investigating the economic and non-economic impact of tourism activities at Pantai Lampuuk, located in Aceh Besar on the community welfare. We employ descriptive analysis based on responded quesionnaires with a total sampel of 30 respondents and conduct in-depth interview with some of the respondents. We find that there is an increase in income substantially after joining tourism business as retailers for consumable foods and providers for accommodation and tourism facilities. Almost fifty percent of the total respondents earn more than IDR 4 millions monthly after getting involved in the business. Monthly spending on staple also drives up approximately more than IDR million, indicating better standard of living.  Moreover, greater access to education and healthier lives are attributable to an increase in income by which parents are able to send their children to higher education, provide good supply of foods and can access to better health services. Based on these positive impacts of tourism, we recommend that the local government to invest more public funds to provide infrastructures in order for domestic and international travelers to get better access to tourism services.